2006
DOI: 10.1213/01.ane.0000242529.96675.fd
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnetic Resonance Imaging to Define the Anatomical Location Closest to All Three Cords of the Infraclavicular Brachial Plexus

Abstract: Infraclavicular techniques are often used to perform brachial plexus blocks. In our volunteer study we used magnetic resonance imaging to identify the brachial plexus and axillary vessels in a sagittal plane corresponding to the lateral sagittal infraclavicular block. In 20 volunteers, all cords were positioned within 2 cm from the artery approximately within 2/3 of a circle. We derived an injection site that was closest to all cords, cranio-posterior and adjacent to the axillary artery. We conclude that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 10 publications
1
59
0
5
Order By: Relevance
“…6b). 28 Several clinical studies have confirmed this hypothesis. 20,29 A fascial click is felt just before reaching the posterior aspect of the artery and signals that the needle tip is in the right location.…”
Section: Infraclavicular Approachmentioning
confidence: 87%
See 1 more Smart Citation
“…6b). 28 Several clinical studies have confirmed this hypothesis. 20,29 A fascial click is felt just before reaching the posterior aspect of the artery and signals that the needle tip is in the right location.…”
Section: Infraclavicular Approachmentioning
confidence: 87%
“…6a). Une étude en résonnance magnétique a évalué qu'un seul point d'injection, situé en postérieur de l'artère axillaire pourrait permettre une diffusion de l'anesthésique local à tous les fascicules 28 (Fig. 6b).…”
Section: Approche Infraclaviculaireunclassified
“…The brachial plexus cords were typically seen in a circumferential manner within the neurovascular sheath at medial, lateral, and posterior locations around the artery. 9 After local anesthetic infiltration to the skin at a cranial location, a block needle (22G 30° short bevel 80 mm Chiba type needle, Havel's Inc., Cincinnati, OH, USA) was introduced along the long axis of the ultrasound probe at a 45° angle. Upon the needle tip reaching the lateral aspect of the neurovascular sheath, a dose of approximately 10 mL of local anesthetic was injected slowly under direct visualization.…”
Section: Methodsmentioning
confidence: 99%
“…If any cord was not stimulated, LA was delivered in the zone (using ultrasound) where that cord presumably resides based on operator experience and a previously described magnetic resonance imaging study. 9 Peripheral nerve block procedure duration was calculated from time of block needle insertion until needle withdrawal. This was to assess if LA dwell times were similar among all 3 groups.…”
Section: Nerve Block Proceduresmentioning
confidence: 99%